China's traditional way of health preservation - Zeng, Qingnan (Foreign Languages Press, 2002)
China's traditional way of health preservation has developed through the accumulated wisdom and experience of thousands of years, and is known throughout the world for its distinctive methods and effects. These methods are often closely related to the daily life of the people. They are simple, safe and effective, as well as being easy to understand and learn. This book is a summary of the many Chinese methods of health preservation, and has been written so as to be understandable and acceptable to Westerners, containing methods which they will find easy to learn and apply. Daily health preserving methods are introduced first, including the seasons, mental attitude, food and drink, entertainment, work, leisure and sex life. The next section contains some 60 different kinds of well-known, easy and effective health preserving methods and exercises, which are all suitable for both the treatment of illness and health preservation. The readers should be able to find whatever he or she needs to fit his or her own daily health needs. The 339 illustrations will help the reader to master the techniques.